(untitled) (Education in the 21st Century, 2025)
Contemporary education is rapidly changing and requires increasing the efficiency of the educational and training process, which is one of the most urgent and important problems of pedagogy at all times. One of the most important requirements for education and training based on the humanistic paradigm is the implementation of an individual approach to learners, their needs, abilities, etc. However, in real practice, there is a contradiction between the frontal forms of teaching and the individual characteristics of the learner, the needs of his/her educational and cognitive activity, which causes the need for differentiation in education, individualization, provision of pedagogical support, support for each student to achieve his/her goals, overcome difficulties, etc. One of the ways to solve these problems is the introduction of innovative technologies that allow taking into account the personal interests and capabilities of learners, which is necessary in the context of the growing diversity of educational needs. And one of the key tools to achieve these goals is tutoring technology. It is defined by certain features inherent to it: individualization, development of special skills, adaptation to changes, etc. In a word, the relevance of this pedagogical technology is justified by the conditions of a rapidly changing educational environment and the fact that it can be effectively applied in schools, HEIs, additional and professional education systems, where an individualized approach is highlighted. The purpose of the research is to reveal the essence of tutoring as an innovative pedagogical technology, to show its opportunities in solving the problems of contemporary education and the challenges at the current stage of educational development. The novelty – tutoring as a pedagogical technology is modernized, its essential characteristics as a pedagogical technology are presented, the opportunities and challenges of introducing this innovative technology in the educational and cognitive process are revealed. Based on a theoretical analysis of scientific research on the presented problem and the results of a sociological survey, it was concluded that the successful introduction of tutoring pedagogical technology can radically change the educational and cognitive process, making it more flexible. Appropriate methodological recommendations have been made.